Antioxidant, aroma, and sensory characteristics of Maillard reaction products from Urechis unicinctus hydrolysates: development of food flavorings - Du, Mengdi; Yu, Wei; Ding, Ning; Jian, Mengqi; Cheng, Yongqiang; Gan, Jing (Frontiers in Nutrition, 2024)
To develop food flavorings with a delicious taste and an anti-oxidation effect, in this study, the glucose Maillard reaction was used for hydrolysates of Urechis unicinctus. The various biological activities of Maillard reaction products (MRPs) and their antioxidant capacity were evaluated. The results showed that the unique fishy odor substances of seafood in MRPs were reduced, indicating that the Maillard reaction improved the flavor of the hydrolysate of Urechis unicinctus. Meanwhile, MRPs exhibited more competitive radical scavenging activities compared to the hydrolysate. Moreover, MRPs demonstrated a considerable potential to protect against 2,2′-Azobis (2-methylpropionamidine) dihydrochloride (AAPH)-induced oxidative stress in a cell model in vitro and in a zebrafish model in vivo. Finally, a novel food flavoring was produced with MRPs as raw material, while the sensory qualities were deemed acceptable. In consequence, during industrial production, MRPs of Urechis unicinctus hydrolysate act as a high-quality raw material for functional flavorings and provide an effective way for the utilization of marine resources.